2011
DOI: 10.1063/1.3663969
|View full text |Cite
|
Sign up to set email alerts
|

Strain dependent resistance in chemical vapor deposition grown graphene

Abstract: The strain dependence of conductance of monolayer graphene has been studied experimentally here. The results illustrate the notable transitions: the slight increase, the dramatic decrease, and the sudden dropping of the conductance by gradually increasing the uniaxial strain. The graphene conductance behaves reversibly by tuning of the elastic tensile strain up to 4.5%, while it fails to recover after the plastic deformation at 5%. The change in conductance due to strain is surprisingly high, which indicates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
176
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(186 citation statements)
references
References 23 publications
9
176
0
Order By: Relevance
“…Cracks were generated in the graphene sheet by application of a tensile loading up to its ultimate tensile strength at room temperature. The recent research of Yu et al found that transferred graphene on PDMS grown by CVD has a higher gauge factor of 151 [46]. This shows that there will be change in resistivity of the graphene with a change in mechanical strain.…”
Section: Potential Application Of Self Healing Phenomena Of Graphenementioning
confidence: 99%
“…Cracks were generated in the graphene sheet by application of a tensile loading up to its ultimate tensile strength at room temperature. The recent research of Yu et al found that transferred graphene on PDMS grown by CVD has a higher gauge factor of 151 [46]. This shows that there will be change in resistivity of the graphene with a change in mechanical strain.…”
Section: Potential Application Of Self Healing Phenomena Of Graphenementioning
confidence: 99%
“…1,2 Strain engineering in graphene is extensively studied because of the possibility of introducing a gap to graphene. 3,4 It has been proven to be feasible to impose uniaxial strain to graphene by stretching or bending the graphene-coated flexible substrates including polydimethylsiloxane (PDMS), 5 polymethyl methacrylate (PMMA) 6 and polyethylene terephthalate (PET). 7,8 However, these investigations are limited to uniaxial strain, and such type of strain is relatively large.…”
mentioning
confidence: 99%
“…Lee et al [21] fabricated a graphene based strain sensor and reported a GF of 6.1 with an applied strain of 1%. The 'transferred graphene' on polydimethylsiloxane (PDMS) has a higher GF of 151 [22]. A reduction in GF with increased unstrained resistance of the sensor and number density of graphene flakes was observed with GNP spray coated sensors [23].…”
Section: Introductionmentioning
confidence: 98%